INT-009 Point Prevalence Studies on Antibiotic Usage at the Children's University Hospital. (12th March 2013) - Sviestina, I; Mozgis, D
Abstract : Background: Due to higher use of broad spectrum agents in the treatment of both adults and children, hospitals are considered to be centres of antimicrobial resistance. According to several studies, approximately 60% of hospitalised children will receive at least one antibiotic. Purpose: To analyse the use of antibiotics at the Children's University Hospital. Materials and Methods: Two point prevalence surveys undertaken on a single day in May and November, 2011. Data collected included demographic details, antibiotic, route and indication. This study included all in-patients, who were present in hospital at 8 am on the days of surveys and to whom a systemic course of antibacterials (ATC J01) were prescribed for treatment. Day-cases were excluded. Microsoft Excel and SPSS 20.0 were used for data analysis. Results: The total number of patients to whom antibacterials was prescribed: 125/418 (30%) in May, and 159/424 (38%) in November. The number of patients to whom antibacterials were prescribed (for treatment): 105 (84%) in May, and 125 (79%) in November. The main age group was 1–5 years: 27 (22%) patients in May, and 33 (21%) in November. Males made up a greater proportion of in-patients. The most common groups of antibiotics prescribed for treatment were extended-spectrum penicillins with 31/117 (27%) treatment courses and the third generation cephalosporins 29 (25%) in May, and 38/158 (24%) and 41 (26%) in November. The top five antibiotics prescribed for treatment were ampicillin, penicillin G, ceftriaxone, cefotaxime and amoxicillin both in May and November. The most common indication for antibiotic treatment was lower respiratory tract infection. Antibiotics were mostly used intravenously: 92 (88%) patients in May, and 109 (87%) in November. Conclusions: These prevalence studies indicated the main problems in antibiotic prescription and areas of improvement: the high use of third generation cephalosporins and predominant intravenous administration. No conflict of interest.